Analysis on the Ability in Writing Poem of Fourth Grade Students at Al Azhar Elementary School Syifa Budi, Marpoyan Damai Subdistrict, Pekanbaru City - Putri, Nia Syamsu (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study is aimed to describe the ability in writing poemof fourth grade students at Al Azhar Elementary School Syifa Budi, MarpoyanDamaiSubdistrict, Pekanbaru City. This research used descriptive quantitative research methods. The research instrument used was a test in writing poem. The data obtained in the ability to write poem is seen from four aspects: number of lines, number of syllables, poetry a-b-a-b and content. Based on the results, from 70 students, there were 57 students who were highly skilled (81.42%), 10 students who were skilled (14.29%), and 3 students who were skilled enough (4.29%), while there is no students in category less skilled. Overall, the ability of students in highly skilled category got an average score of 91%. This shows that the ability of fourth grade students of Al Azhar Elementary School Syifa Budi in MarpoyanDamaiSubdistrict, Pekanbaru City in writing poem as a whole is